Minimising sunburn necrosis on Vitis vinifera L. ‘Riesling’ grapes by defoliation, photo- and thermal protection - Jonas Waber; Kai Konstantin Heilemann; Kristina Heilemann; Mareike Schultz; Christopher Simon; Günther Buchholz; Raúl Losantos; Iris Alicia Bermejo; Diego Sampedro; Matthias Petgen; Ulrich Fischer; Patrick Winterhagen; et al. (OENO One)
Sunburn on grapes has emerged as an economic concern in recent decades. The phenomenon can be attributed to climatic changes, characterised by elevated air temperatures and intense solar radiation, leading to increased crop failures as well as quality losses of wines. This study aimed to evaluate comprehensively selected preventive strategies for the sunburn-sensitive, white cultivar ‘Riesling’. To this end, the impact of the timing of bunch zone defoliation on sunburn necrosis within three wine-growing regions in Central Europe, as well as the application of sunscreens onto grapes and shading by protective nets at one of these sites, were visually assessed in the contrasting growing seasons 2021 and 2022, respectively. Early defoliation between the end of flowering and fruit set decreased sunburn necrosis severity by down to 59.6 % in comparison to late defoliation at bunch closure across the two years. Furthermore, rot severity was reduced by down to 85.3 % in comparison to no defoliation across both growing seasons. The application of lime onto grapes following late defoliation diminished sunburn damage by 41.9 % across both experimental years, while kaolin showed no effect. Combining early defoliation with application of lime revealed an increased effectiveness of 79.2 % in comparison to late defoliation within one growing season. Different protective nets were able to lower sunburn damage within each growing season, but the black, small-meshed shading net with the highest shading factor investigated revealed the highest effectiveness of 63.7 % across both experimental years. However, the effectiveness of defoliation, sunscreens and protective nets depended on the meteorological conditions during each growing season. Total yield, including grapes with different levels of damage, as well as the vigour of vines, were not impacted by the viticultural measures. Malic acid and total acidity concentrations in the must were decreased by early defoliation compared to no defoliation within each year, while must weight was not influenced by any measure. In conclusion, this study compared the potential of different prevention strategies and highlighted a combined positive effect of early defoliation at two experimental sites and within each growing season: Both sunburn necrosis and rot severity were reduced in comparison to the respective maximum extent.